Unique finding in congenital muscular torticollis: Clinic screening on the neck of one day old neonate and ultrasonographic imaging from birth through 3 years of follow-up. Issue 11 (March 2019) - Xiong, Zhu; Zeng, Shuaidan; Chen, Huanxiong; Qiu, Xin; Tang, Gen; Tang, Yu; Tang, Shengping
Abstract : Abstract: Congenital muscular torticollis (CMT) is a common musculoskeletal abnormality in children, which has been characterized by unclarified pathological changes in the sternocleidomastoid muscle (SCM) and various hypothetical etiologies. There are 2 main hypothetical etiologies for CMT in the literature: 1 infers that CMT may represent the sequela of an intrauterine or perinatal compartment syndrome, and the other regard CMT as a maldevelopment of the fetal SCM. To better understand the etiopathogenesis of CMT, we screened the necks of 1-day-old newborns that may potentially have CMT for evidence of SCM trauma or tumor. A convenience sample of 2564 full-term (>37 weeks) Chinese neonates were included in this study. All neonates were screened for CMT by physical examination at birth. If CMT was suspected, further ultrasonic and physical examinations were performed. When CMT was confirmed, we provided appropriate interventions and follow-up. The progress and changes in patients with CMT were recorded. Following physical examination, 44 of 2564 neonates were diagnosed with suspected CMT based on obvious facial asymmetry or palpable swelling or mass in the SCM. Among these, ultrasound examination showed 81.8% (36/44) had asymmetry in the thickness of the bilateral SCM. The 36 neonates were followed-up for 6 months; among them, 1 infant developed CMT and 35 showed normal development in bilateral SCM. The 1 patient with CMT underwent regular physiotherapy and recovered with no evidence of recurrence after the final 3 years of follow-up. No neonates suffered from signs of neck trauma, such as hematoma or subcutaneous ecchymosis. There was no evidence of neck trauma in this 1 day old newborn. The pseudotumor of SCM that developed after birth underwent differentiation, maturation, and disappeared as the baby grew. The SCM asymmetry did exist in some of the newborn babies, and became symmetric with the baby's growth. Data from this clinical study and our previous ultra-structural pathological studies suggested that both prenatal and postnatal factors play important roles in CMT. We hypothesized that CMT might be a developmental disease.